B05 New Light On The Role Of Calpain-mediated Proteolysis Of Mutant Huntingtin. (17th September 2014) - Jeremiasz Weber, J; Gierke, M; Klumpp, L; Singer, E; Clemens, LE; Walter, C; Huber, SM; Riess, O; Nguyen, HP
Abstract : Background: Calpains (CAPNs), a class of intracellular calcium-dependent cysteine proteases, belong to the group of proteolytic enzymes which have been associated with the cleavage of mutant huntingtin (Htt), the source for toxic fragments of the disease protein. As excitation-induced calcium influx occurring in neurons can activate CAPNs and excitotoxicity represents an important factor in the pathomechanism of Huntington's disease (HD), these proteases might explain the neuronal determination of the disease. Aims: To improve our knowledge on the involvement of CAPNs in the molecular mechanism of HD pathogenesis by examining the impact of different members of the CAPN system and by dissecting linked activation pathways. Methods: The CAPN system and proteolytic fragmentation of Htt were analysed in different in vitro and in vivo models of HD via protein biochemical and calcium imaging techniques. Results: We observed an over-activation of the CAPN system in cell and mouse models of HD. Activation of CAPNs in cell-free and cell-based assays promoted the fragmentation of wild type and mutant Htt generating specific N- and C-terminal fragments. Conversely, suppressing CAPN activity using specific inhibitors improved the viability of STHdh Q111 cells. These results stress the importance of CAPNs on mutant Htt cleavage and disease development. Conclusions: Our enhanced understanding of calpain-mediated proteolysis as a key event in the molecular pathogenesis of HD, will promote the quest for new therapeutical targets as a treatment for this fatal disease.